The Effect of E-Learning Resources on Image and Implications on Trust (Study at Open University in Indonesia) - Joko Rizkie Widokarti; Ginta Ginting (Journal of Economics, Business, and Government Challenges, 2020)
This study aims to examine the effect of e-learning resources on images, the influence of e-learning resources trusts, the influence of images on trusts, and the influence of e-learning resources trusts through images. This research uses quantitative research methods. Time horizon is cross sectional, because it is done at a certain time. The unit of analysis is the Open University with the observation unit being students from the Open University, with a sample of 300. The analytical design used to test hypotheses and determine the relationship between research variables is Structural Equation Modeling (SEM). The results showed that E- learning resources also affect the image of the trust. Image affects trust. The development of trust in E-learning is more dominantly built by images, and images are built by e-learning resources. The results of this study have implications for university management in the development of e-learning that increasing trust needs to be built by efforts to improve image. To develop an image, it is necessary to build adequate e-learning resources that are built with the development of tangible assets and intangible assets